Comprehensive Comparative Analysis and Innovative Exploration of Green View Index Calculation Methods - Dongmin Yin; Terumitsu Hirata (Land)
Despite the widespread use of street view imagery for Green View Index (GVI) analyses, variations in sampling methodologies across studies and the potential impact of these differences on the results, including associated errors, remain largely unexplored. This study aims to investigate the effectiveness of various GVI calculation methods, with a focus on analyzing the impact of sampling point selection and coverage angles on GVI results. Through a systematic review of the extensive relevant literature, we synthesized six predominant sampling methods: the four-quadrant view method, six-quadrant view method, eighteen-quadrant view method, panoramic view method, fisheye view method and pedestrian view method. We further evaluated the strengths and weaknesses of each approach, along with their applicability across different research domains. In addition, to address the limitations of existing methods in specific contexts, we developed a novel sampling technique based on three 120° street view images and experimentally validated its feasibility and accuracy. The results demonstrate the method’s high reliability, making it a valuable tool for acquiring and analyzing street view images. Our findings demonstrate that the choice of sampling method significantly influences GVI calculations, underscoring the necessity for researchers to select the optimal approach based on a specific research context. To mitigate errors arising from initial sampling angles, this study introduces a novel concept, the “Green View Circle”, which enhances the precision and applicability of calculations through the meticulous segmentation of observational angles, particularly in complex urban environments.